(untitled) (Conferencea, 2024)
On the epidemiology of tumors in children, the leading pediatric oncologists of different countries in all their work consider the relationship of malignant tumors with obstetric pathology, viral infections of the mother during pregnancy, vaccination of mothers during pregnancy, congenital and family factors, gender and age, developmental defects.